Seeking a common path: structuring multistakeholder dialogue on agricultural biotechnology in Africa - von Grebmer, Klaus; Omamo, Steven Were (International Food Policy Research Institute, 2006)
In southern Africa, as in other parts of the world, agricultural biotechnology—particularly the production, consumption, trade, and transport of genetically modified (GM) foods—has been steeped in controversy. The divergent and sometimes contradictory positions are grounded in deep-seated beliefs about technology, the environment, the global order, and the meaning of development among the various stakeholders. This paper seeks to explain the arguments that underlie the different positions taken by national and regional stakeholders, including representatives of public bodies, the private sector, and civil society, on the role of biotechnology. It describes efforts to develop a common process for discussion of the issues. The aim of the dialogue is to agree on the process, rather than to develop consensus.